(3GdYeOI aj UfGYI GdTYQ hfbOgs - (3GdMSf Hf QTjb GdbjQhGfj, CHh Ydj , GHf QTjb,J (B463 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Cgd GdMeO heSJMbI CeG HYO aEf CMb ef Lfi KeQ GdCdHGH hGbJWa RgQ GdBOGH ef YQa ddYde Mbg hbO hLOJ GdTYQ dCcHQ Yde ddYQH aLeYJ CMSf eG bGdg cd hGMO efge ai cJGHg s
(3BNQgG (B:s
(3GdeQGO UOQ GdHjJ dGYLRg , hEPG ONd GdJLfS fai YO WHGbkG , hcPdc GdWHGb jUjQ HGdfai JLfjSkG , hSCaQO dgeG HGHkG ajeG HYO Ef TGA Gddg JYGdi s
(3HBNQgG agQSJ HCHhGH GdeLdO GdChd hCHhGH GdeLdO GdKGfi GdPi jdjgs
(3Hg eWGdH ddcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B191 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B225s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdHdGZIs